Iris metastasis of diffuse large B-cell lymphoma misdiagnosed as primary angle-closure glaucoma: A case report and review of the literature - Li Zebing (De Gruyter, 2021)
Lymphoma with intraocular metastasis is an uncommon and serious disease. We describe a case of diffuse large B-cell lymphoma (DLBCL) with iris metastasis. Meanwhile, we refer to published case reports retrieved via a PubMed search to summarize this rare disease.